The utility of endobronchial ultrasound-transbronchial needle aspiration in lymphoma - Kheir, Fayez (Endosc Ultrasound, 2016)
BACKGROUND AND OBJECTIVES: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive procedure that has a well-established role in the diagnosis and staging of lung cancer. This technology is also widely used for the diagnosis of mediastinal masses and cysts as well as other inflammatory disorders such as sarcoidosis. However, the utility of this procedure in the diagnosis and subclassification of lymphoproliferative disorders (LPDs) is not clear. We performed a systematic review to evaluate EBUS-TBNA use in LPDs. MATERIALS AND METHODS: PubMed, EMBASE, MEDLINE, Cochrane Library Plus, and ISI Web of Knowledge were searched for studies of clinical trials in English reporting diagnostic performance of EBUS-TBNA in lymphoma until September 2014. The overall sensitivity, negative predictive value (NPV), and diagnostic accuracy were evaluated. RESULTS: Six trials involving 346 patients with suspected lymphoma were included. The overall sensitivity, NPV, and diagnostic accuracy ranged 38%-91%, 83%-96.4%, and 91%-97%, respectively. Further invasive surgery was needed only in 13-43% of the patients. None of the studies included in the present review reported important complications. CONCLUSION: Current evidence suggests that EBUS-TBNA can be used as an initial evaluation for patients with suspected lymphoma. Additional surgical procedures may be necessary if a sample is inadequate or negative with high suspicion of lymphoma. Further multicenter trials are needed to evaluate the diagnostic yield of EBUS-TBNA in lymphoma patients.